Key clinical applications for indocyanine green fluorescence imaging in minimally invasive colorectal surgery - Grosek, Jan (J Minim Access Surg, 2020)
Near-infrared indocyanine green (ICG) fluorescence imaging has gained solid acceptance over the last years, and rightly so, as this technology has so much to offer, especially in the field of minimally invasive surgery. Firm evidence from ongoing and future studies will hopefully transform many of the applications of ICG fluorescence into the standard of care for our patients. This review examines the current status of ICG fluorescence for assessment of bowel perfusion, lymphatic mapping as well as intraoperative localisation of ureter in light of the published academic literature in English.